Rapid development and implementation of a behaviour change strategy to improve COVID-19 personal protective equipment use in a regional Australian emergency department. (December 2022) - Curtis, Kate; Jansen, Peter; Mains, Margot; O'Hare, Anna; Scotcher, Bradley; Alcorn, David; Nahidi, Shizar; Harris, Joanna; Brouillard, Daniel; Morton, Sarah; Shaban, Ramon Z.
Abstract: Objective: To identify barriers to, describe the development of and evaluate the implementation of a behavioural theory informed strategy to improve staff personal protective equipment (PPE) compliance during COVID-19 in a regional Australian Emergency Department. Methods: Barriers to PPE use were identified through staff consultation then categorised using the Theoretical Domains Framework. The Behaviour Change Wheel was used to develop a strategy to address the barriers to PPE compliance. The strategy was refined and endorsed by the site COVID taskforce. Data were collected through direct observation. Descriptive statistics were used to summarise PPE compliance and inductive content analysis for free text data of staff behaviours. Results: 73 barriers were identified, mapped to 9 intervention functions and 42 behaviour change techniques. The predominant mechanisms were: (1) Executive communication reinforcing policy and consequences; (2) implementation of a PPE Marshal; (3) face to face reinforcement / modeling; (4) environmental restructuring including electronic medical record modifications. The PPE Marshal observed 281 PPE activities. PPE compliance varied between 47.9% (Buddy check) and 91.8% (Bare below elbow). The PPE Marshal intervened on 121 occasions, predominantly through buddying, explaining and demonstrating correct PPE use, most frequently with medical staff (72%). Conclusion: We describe an evidence-based process to overcome barriers to PPE compliance that maximize safe work practice in a time critical situation. Staff require enabling, access to equipment and reinforcement to use PPE correctly.